2022
DOI: 10.3389/fonc.2022.962473
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of blood-derived exosomal hTERT mRNA as a biomarker for colon cancer and Lynch syndrome

Abstract: BackgroundHuman telomerase reverse transcriptase (hTERT)- mRNA was shown to be elevated in exosomes derived from the sera of a variety of hematological and solid cancer patients. We aimed to evaluate its role as a diagnostic marker in patients with newly diagnosed colon cancer and in hereditary syndromes with predisposition to colon cancer.MethodshTERT -mRNA levels were determined in serum-derived exosomes from 88 patients with colon cancer, 71 Lynch-syndrome carriers with unknown active malignancies and 50 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Our results suggest that the proportion of high levels of circulating telomerase transcript correlate with the extent of tumor malignancy and might serve as an indicator of oncogenic activity. These findings are in line with previous publications showing a similar phenomenon of increasing presence of circulating hTERT transcript with increasing tumor grade in both colorectal cancer 22 and hepatocellular carcinoma (in preparations). Furthermore, our findings in meningiomas and glioblastomas suggest that it also has the potential to serve as a clinical biomarker.…”
Section: Discussionsupporting
confidence: 93%
“…Our results suggest that the proportion of high levels of circulating telomerase transcript correlate with the extent of tumor malignancy and might serve as an indicator of oncogenic activity. These findings are in line with previous publications showing a similar phenomenon of increasing presence of circulating hTERT transcript with increasing tumor grade in both colorectal cancer 22 and hepatocellular carcinoma (in preparations). Furthermore, our findings in meningiomas and glioblastomas suggest that it also has the potential to serve as a clinical biomarker.…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, the levels of the hTERT transcript were correlated with levels of carcinoembryonic antigen (PSA) in patients with colorectal cancer and significantly differed from those of patients with polyps that served as a control group. In this study, we also measured the levels of the hTERT transcript in patients with Lynch syndrome, which is associated with a predisposition to colorectal cancer, and found positive levels of hTERT transcripts in several carriers [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the identification of hTERT transcripts in the plasma of CRC patients may serve as a useful tool for disease monitoring, as mRNA levels correlate with those found in tumors [ 208 ]. The prognostic and predictive significance of cell-free circulating hTERT has been evaluated in CRC patients in detail [ 207 , 209 , 210 ]. Bertorelle et al showed that stage II CRC patients with lower levels of hTERT had better OS, while its presence at higher levels was correlated with a poor response to chemotherapy (as an independent prognostic factor) and with a higher risk of disease recurrence and death [ 207 ].…”
Section: Telomerase Activity and Crcmentioning
confidence: 99%
“…It has been shown that a variety of both normal and neoplastic cells can secrete them (among which are CRC cells) into the microenvironment from where they enter the bloodstream. Exosomes offer the advantage that their mRNA content is not exposed to the activity of extracellular RNases, allowing for reliable estimation [ 210 ]. In summary, ample evidence supports telomerase as a useful marker for monitoring and predicting outcomes in CRC [ 207 ].…”
Section: Telomerase Activity and Crcmentioning
confidence: 99%